A retrospective analysis of the clinical characteristics of 207 hospitalized children with adrenal masses - Zhang, Kaiping; Zhang, Ye; Zhang, Yin; Chao, Min (Frontiers in Pediatrics, 2023)
Objective: The detection rates of adrenal mass (AM) have recently increased. The study was to examine the clinical characteristics of these adrenal masses for guiding the clinical diagnosis and treatment among hospitalized children. Methods: The clinical data of AM, admitted in our hospital from January 2014 to March 2023, were collected and analyzed retrospectively. The data included composition, gender, age, initial presentation, size and site of mass, functional tumor, intervention or surgery, pathological or clinical diagnosis and imaging data. Results: A total of 207 hospitalized children were included. Among them, adrenal hematoma was the most common finding (53.6%), followed by adrenal neuroblastoma (36.2%). Most masses are larger sized (51.2%) and non-functional (94.7%). We found that adrenal hematoma commonly occurred in a neonate or child with abdominal trauma. Most cases were found in male (63.1%), right-side (71.2%) and size < 4cm (73.9%). Adrenal neuroblastoma was commonly detected in male (56.0%), right-side (66.7%) and size ≥ 4cm (85.3%). Moreover, the metastases were frequently explored at the time of diagnosis. In addition, there was no significant difference between ultrasound and computed tomography (CT) scan under suspicion of hematoma (P0.05). However, CT showed a priority over ultrasound in the diagnosis of neuroblastoma (P＜0.05). Conclusion: Most masses were non-functional and benign. Of these, adrenal hematoma was the most common AM, followed by adrenal neuroblastoma in pediatric AM. They were both commonly found in male and right-side. Neuroblastoma revealed a larger tumor size. Compared to hematoma, adrenal neuroblastoma required CT scan for further assessment.